"Academic guilt": The impact of the pandemic-enforced lockdown on women's academic work. (September 2021) - Walters, Cyrill; Ronnie, Linda; Jansen, Jonathan; Kriger, Samantha
Abstract: According to anecdotal accounts, the guilt engendered by the conflict between employment and family that is pervasive in the academy (or "academic guilt, " in this paper) has been exacerbated by the COVID-19 pandemic-enforced lockdown. To date, there has been no systematic research that provides a detailed account of, and explanations for, the "academic guilt" experienced by women academics, in particular, outside of the Global North. The research team conducted a large-scale systematic survey of all female academic staff in a nationwide study of South Africa's 26 public universities during the period of the lockdown. A total of 2029 full responses were received from women at different stages in their academic careers. The survey included an open-ended section that allowed for detailed, unlimited responses by the participants; this section provided a substantial volume of qualitative data, which was coded and analyzed. Leveraging the richness of the open-ended survey data, this study presents findings showing significantly high feelings of "academic guilt" among women academics during the pandemic-enforced lockdown for a variety of reasons relating to the working conditions imposed by the lockdown mandates.